Almgren Group VII, Series I Brooches in Sarmatian Graves of the North-Western Pontic Region* - Batog, Nicolai (Revista Arheologică, 2026)
This study examines two Sarmatian graves from the north-western Pontic region – Holmskoe grave 19 and Hlinaia tumulus 38, grave 2 – in which brooches belonging to the wider Almgren Group VII, Series I horizon were discovered. It argues that both finds belong to the same broad typological field, but do not occupy the same internal position within it: the Hlinaia specimen belongs more clearly to the headknob and external-chord branch, whereas the Holmskoe pair represents the knobless external-chord variant, close to Almgren 193, and is cautiously integrated here into the later Cociș-Bârcă framework as B1a1b1. Questions of origin and circulation provide the broader interpretative background, while the funerary contexts clarify how these brooches acquired meaning in specific graves. For this reason, the article connects typological analysis with funerary context, comparing the deposition of a single brooch with deposition in pairs and highlighting the principal typological frameworks relevant to the interpretation of these finds. The two graves thus show that the bearers of Sarmatian culture in the region actively participated in the interregional circulation and reinterpretation of ornaments within the post-Marcomannic horizon.